1984
DOI: 10.1021/jo00198a005
|View full text |Cite
|
Sign up to set email alerts
|

Acid-catalyzed nitronate cycloaddition reactions. Useful syntheses and simple transformations of 3-acyl- and 3-alkenylisoxazolines

Abstract: Nitronic esters derived from primary nitro ketones, ethyl nitroacetate, and (phenylsulfonyl)nitromethane react with dipolarophiles in the presence of nonaqueous protic and Lewis acids to give nitrile oxide cycloadducts. a-Nitro ketones, ethyl nitroacetate, and (phenylsulfonyl)nitromethane give nitrile oxide cycloadducts in the presence of p-toluenesulfonic acid, although conditions are necessarily more vigorous. The anions of phenylnitromethane and 1-nitropropane react similarly under mild conditions, the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The enhanced reactivity of 1a and 1b compared to nitro compounds 1c, 1d and 1f has already been noticed and is related to the ability of the carbonyl group to enolize. [51] Phenylsulfonylnitromethane (1d) appears particularly sluggish in this reaction.…”
Section: Discussionmentioning
confidence: 95%
“…The enhanced reactivity of 1a and 1b compared to nitro compounds 1c, 1d and 1f has already been noticed and is related to the ability of the carbonyl group to enolize. [51] Phenylsulfonylnitromethane (1d) appears particularly sluggish in this reaction.…”
Section: Discussionmentioning
confidence: 95%
“…We therefore prepared this com- pound from benzoylnitromethane (1) following a literature procedure [14] and submitted it to the same reaction conditions (DABCO, water and chloroform at 60°C). Without the dipolarophile, benzoic acid was the sole identified product, whereas in the presence of the dipolarophiles norbornene (2a), styrene (2b) or phenylacetylene (2c) furoxan 7 was mainly converted into the furazans 5a (70 %) 5b (50 %), and 5c (41 %), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Wade and co-workers 26 reported that acid-catalyzed nitronate cycloaddition reactions gave 4,5-dihydroisoxazole and isoxazole derivatives from nitro compounds and dipolarophiles. In this reaction, nitronic esters were transformed from primary nitro ketones in the presence of nonaqueous protonic and Lewis acids or a strong acid.…”
Section: Resultsmentioning
confidence: 99%